Phenotypic and genomic analyses of bacteriocin-producing probiotic Enterococcus faecium EFEL8600 isolated from Korean soy-meju - Kim, Da Hye; Kim, Seul-Ah; Jo, Na Gyeong; Bae, Jae-Han; Nguyen, Minh Tri; Jo, Yu Mi; Han, Nam Soo (Frontiers in Microbiology, 2023)
Enterococcus faecium is a prevalent species found in fermented soybean products, known for its contributions to flavor development and inhibition of pathogenic microorganisms during fermentation. This study aims to provide comprehensive phenotypic and genomic evidence supporting the probiotic characteristics of E. faecium EFEL8600, a bacteriocin-producing strain isolated from Korean soy-meju. Phenotypic analysis revealed that EFEL8600 produced a peptide with inhibitory activity against Listeria monocytogenes, estimated to be 4.6 kDa, corresponding to the size of enterocins P or Q. Furthermore, EFEL8600 exhibited probiotic traits, such as resilience in gastrointestinal conditions, antioxidant and anti-inflammatory activities, and protection of the intestinal barrier. Safety assessments demonstrated no hemolytic and bile salt deconjugation activities. Genomic analysis revealed the presence of several genes associated with probiotic characteristics and bacteriocin production, while few deleterious genes with a low likelihood of expression or transferring were detected. Overall, this study highlights E. faecium EFEL8600 as a potent anti-listeria probiotic strain suitable for use as a starter culture in soymilk fermentation, providing potential health benefits to consumers.